The differences of achievement of the national olympiad in chemistry at the public and private senior high school by utilizing quizizz media - Leony Sanga Lamsari Purba; Nelius Harefa; Sali Afridika; Dera Savera (Pascasarjana Universitas Negeri Medan, 2021)
This research is a quantitative study which aims to determine the results differences of the 2nd National Chemistry Olympiad at the public and private senior high school using quizizz media. All participants of the population were sampled in the determination, the sampling technique used was saturated samples. The results of the prerequisite test on the data from this study showed that the data were normally and homogeneous. For normality and homogeneity tests, obtained sig > 0.05. Data analysis using SPSS 24, carried out One Way Anova test, obtained sig.0.01 with a significance level of 5%, these results indicate that there are differences in the results of the 2nd National Chemistry Olympiad (OKN) level is low, the public high school participants results with an average score of 59.48 and private high schools with an average score of 41.95 by utilizing Quizizz media.Keywords: Chemistry, Olympics, Learning, Quizizz